PERAN BADAN LINGKUNGAN HIDUP KOTA PEKANBARU DALAM PEMBERIAN IZIN LINGKUNGAN PERHOTELAN DI KOTA PEKANBARU - Ilham Akbar Saputra; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this study was to determine the extent of the role of the Environment Agency of Pekanbaru in granting an environmental permit hospitality in the city of Pekanbaru. Which is the number of hotels operating in the city of Pekanbaru in 2013 was 138, while the hotel has an environmental permit only reached 59.This study is a qualitative study conducted in the city of Pekanbaru implemented, namely the Environment Agency Pekanbaru. Source of research data obtained from the Environment Agency employee Pekanbaru city. Presentation of data in narrative form, in-depth stories of the informants who are considered able to provide information about the study and review of the literature. After the data collected were analyzed using qualitative descriptive analysis.After doing research, it was found that the role of the Environment Agency in Pekanbaru city licensing pekanbaru hospitality in the city can still be carried out to the maximum. Because there are some things that become barriers.Keywords: the role, Permits hospitality environment, the Environment Agency